Mapping a Partial Andromonoecy Locus in Citrullus lanatus Using BSA-Seq and GWAS Approaches - Aguado, Encarnación; García, Alicia; Iglesias-Moya, Jessica; Romero, Jonathan; Wehner, Todd C.; Gómez-Guillamón, María Luisa; Picó, Belén; Garcés-Claver, Ana; Martínez, Cecilia; Jamilena, Manuel (Frontiers in Plant Science, 2020)
The sexual expression of watermelon plants is the result of the distribution and occurrence of male, female, bisexual and hermaphrodite flowers on the main and secondary stems. Plants can be monoecious (producing male and female flowers), andromonoecious (producing male and hermaphrodite flowers), or partially andromonoecious (producing male, female, bisexual and hermaphrodite flowers) within the same plant. Sex determination of individual floral buds and the distribution of the different flower types on the plant, are both controlled by ethylene. A single missense mutation in the ethylene biosynthesis gene CitACS4, is able to promote the conversion of female into hermaphrodite flowers, and therefore of monoecy (genotype MM) into partial andromonoecy (genotype Mm) or andromonoecy (genotype mm). We phenotyped and genotyped, for the M/m locus, a panel of 207 C. lanatus accessions, including 5 inbreds and hybrids, and found several accessions that were repeatedly phenotyped as PA (partially andromonoecious) in several locations and different years, despite being MM. A cosegregation analysis between a SNV in CitACS4 and the PA phenotype, demonstrated that the occurrence of bisexual and hermaphrodite flowers in a PA line is not dependent on CitACS4, but conferred by an unlinked recessive gene which we called pa. Two different approaches were performed to map the pa gene in the genome of C. lanatus: bulk segregant analysis sequencing (BSA-seq) and genome wide association analysis studies (GWAS). The BSA-seq study was performed using two contrasting bulks, the monoecious M-bulk and the partially andromonoecious PA-bulk, each one generated by pooling DNA from 20 F2 plants. For GWAS, 122 accessions from USDA gene bank, already re-sequenced by genotyping by sequencing (GBS), were used. The combination of the two approaches indicates that pa maps onto a genomic region expanding across 32.24-36.44 Mb in chromosome 1 of watermelon. Fine mapping narrowed down the pa locus to a 867 Kb genomic region containing 101 genes. A number of candidate genes were selected, not only for their function in ethylene biosynthesis and signalling as well as in flower development and sex determination, but also by the impact of the SNPs and indels differentially detected in the two sequenced bulks.